JASMINE FLOWERS IN JAVANESE MYSTICISM - Lestari, Nanny Sri (International Review of Humanities Studies, 2019)
This study discusses Javanese society's awareness of jasmine flowers (jasminum sambac) which are small in shape but have full of cultural meanings and philosophies, thus becoming a symbol of life. The focus of this study is the physical form of jasmine flowers and awareness of a healthy natural environment that can build a healthy mental (soul). The purpose of this study is to explore the unique small flower of jasmine, which has long been a symbol of awareness of environmental health which is not only physical but also mental (soul). This study uses a theoretical framework of health, the natural environment and Javanese mysticism, to see the relationship between humans and their environment. This study uses a qualitative research paradigm procedure. Qualitative research procedures provide opportunities for researchers to provide interpretations of the results of their research. The results showed that, ideologically, Javanese people were indeed aware of the importance of the natural environment. The natural environment is the most important factor in human life. Through daily activities can be seen and interpreted that Javanese humans cannot escape from their natural environment. Jasmine small white flowers and it turns out to save many benefits in physical and mental health. Through the cultural roots that exist in cultural ritual activities can be seen, an effort to preserve small white flowers that have many benefits. With positive benefits can give birth to a philosophy that captures the meaning of the flower in life